Evolution of full-scale pore structure characteristics of long-flame coal and influencing factors - Zheng Zhang; Shuguang Yang; Gang Wang (Fuel Processing Technology)
China has vast long-flame coal reserves containing abundant coalbed methane (CBM) resources. Understanding the evolution of full-scale pore structure characteristics of this coal and their influencing factors are vital for the CBM development. However, researches on these topics are limited. Herein, 17 long-flame core coals were collected from southern Junggar Basin to accurately characterize the specific surface area (SSA), total pore volume (Vt), and full-scale pore size distribution (FPSD) using mercury intrusion porosimetry (MIP) along with N2/CO2 adsorption experiments. Results demonstrate that the FPSD generally exhibits a bimodal characteristic, with abundance of micropores and macropores but scarcity of mesopores, which hinders the efficient transport of CBM. The full-scale pore structure characteristics are closely linked to coal's thermal evolution. As Ro, max rises, Vt, mesopore volumes (Vme), and macropore volumes (Vma) initially decrease to a minimum at a Ro, max of ∼0.55 % and then increase. Conversely, micropore volumes (Vmi) exhibit an inverted U-type correlation with Ro, max, peaking almost at the same Ro, max. Ash yield negatively affects pore volumes and SSAs, particularly for macropores. Inertinite-rich long-flame coals, particularly those with higher semifusinite and fusinite contents, develop more micropores and mesopores, whereas increasing vitrinite content is negatively correlated with their development.